2003
DOI: 10.1074/jbc.m210159200
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Characterization of the Human DNA Repair Helicase XPD by Comparative Molecular Modeling and Site-directed Mutagenesis of the Bacterial Repair Protein UvrB

Abstract: A molecular model for the human nucleotide excision repair protein, XPD, was developed based on the structural and functional relationship of the protein with a bacterial nucleotide excision repair (NER) protein, UvrB. Whereas XPD does not share significant sequence identity with UvrB, the proteins share seven highly conserved helicase motifs that define a common protein structural template. They also have similar functional roles in their ATPase activity and the ability to unwind DNA and verify damaged strand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 62 publications
2
34
0
2
Order By: Relevance
“…Interestingly, the equivalent Asp338Asn mutation in XPD, the human analogue of UvrB, has been found to be highly prevalent amongst xeroderma pigmentosum patients. Based on the molecular modelling studies described by Bienstock et al, 22 we also note that Lys67, invariant amongst the bacterial UvrB homologues, is replaced by threonine (Thr76) in XPD. A Thr76Ala mutation has been found in xeroderma pigmentosum sufferers, presenting the possibility that there may be functional conservation of this residue where the hydroxyl group of Thr76 could mediate interactions similar to those of the sidechain N z moiety of Lys67 in UvrB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the equivalent Asp338Asn mutation in XPD, the human analogue of UvrB, has been found to be highly prevalent amongst xeroderma pigmentosum patients. Based on the molecular modelling studies described by Bienstock et al, 22 we also note that Lys67, invariant amongst the bacterial UvrB homologues, is replaced by threonine (Thr76) in XPD. A Thr76Ala mutation has been found in xeroderma pigmentosum sufferers, presenting the possibility that there may be functional conservation of this residue where the hydroxyl group of Thr76 could mediate interactions similar to those of the sidechain N z moiety of Lys67 in UvrB.…”
Section: Discussionmentioning
confidence: 99%
“…Arg543 has been shown to be an essential residue in repair, since its mutation to histidine results in a protein that is repair-deficient, exhibiting a loss of helicase activity and ATPase stimulation by DNA in the presence of UvrA. 22 Although its role has been speculated upon, from our structure it would appear that Arg543 functions to stabilise the product and possibly substrate complexes.…”
Section: Adp Binding and Implications For Both Catalysis And Signal Tmentioning
confidence: 95%
“…We have shown previously that the D510A UvrB mutant is defective in UvrA⅐DNA damagedependent ATPase activity leading to a loss of incision efficiency (43). This mutant does not form a UvrB⅐DNA complex as determined by EMSA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The two polymorphisms have shown little or no effect on the protein using predictive models [4] or evolutionary analysis [5]. Structural evidence indicated that these polymorphisms are located outside the main catalytic sites [6] and far from regulatory [7] and interacting domains [8] suggesting that they have no direct effect on the ATPase activity of ERCC2. Additional studies detected no measurable effect of the two variants on NER capacity and basal transcription activation [2], and genotype-specific differences in DNA repair rates was inconsistent [9].…”
Section: Introductionmentioning
confidence: 97%